Impact of physical activity on incidence of osteoporotic fractures - a review - Paweł Oszczędłowski; Kacper Niewęgłowski; Barbara Madoń; Justyna Nowaczek; Adrian Giermasiński (Kazimierz Wielki University, 2021)
Introduction and purpose: The purpose od this study is to describe influence of participating in sporting activities on health of the bones. Osteoporosis is a disease of elderly people in which bone mineral density lowers. Physical activity was reported to increase bone mineral density. A brief description of the state of knowledge: Better physical performance is a positive factor that lowers the possibility of fracturing the bones of the elderly. Another factor that plays protective role is lean body mass and development of muscles. Training in young age can help to increase the bone mineral density, but the effect ceases with the passing of time, being much lower after decades. Multiple genes have impact on bone mineral density of the individual. Professional athletes have usually higher bone mineral density, but accumulation of microdamage in their bones can result in stress fractures. Training in elderly age is proven to increase bone mineral density of an individual, especially performing weight-bearing sports. Conclusions: Physical activity has been proven to positively affect health in many ways. One of them is strengthening the bones by increasing bone mineral density. As it increases, the possibility to break the bone lowers, which makes it an effective way to support the fight against the osteoporosis. It is especially important for women, who are more susceptible to osteoporotic fractures in post-menopausal age.